The finite element analysis of behavior of bolted column to I-beam connected with channel stiffeners - Lee, Jin Yeow (2012)
Steel channel as stiffeners is a new stiffening method proposed for moment-resisting beam-to-column connections of steel frames, to meet some architectural needs. This method uses bolted channels as alternatives to both continuity and double plates. This study investigates the behavior of bolted column to I-beam connected with channel stiffeners in steel frames by using finite element analysis (FEA). From the FEA analysis, utilizing LUSAS 14.0.3 software, the interaction between the type of column stiffeners and column flange bolted to beam connections, as well as geometric and material have been considered. Five models had been conducted in this project by using FEA software. Based on the results of FEA, the stress-strain relationship and behavior of bolted column to I-beam connected with channel stiffeners has been presented. Besides, the buckling loads and deformed shapes of the bolted column to I-beam influenced by type of stiffeners have been illustrated. Conclusions are given as that steel channel stiffeners used in steel frames are improve the performance of column connections, but less effective compared with traditional steel plate stiffeners.